Hubungan Kepatuhan Pekerja Menggunakan Alat Pelindung Diri dengan Kejadian Kecelakaan Kerja di PT PLN Persero APP Cawang Tahun 2017 - Deli Mika Mardison; Sariah Sariah (Jurnal Persada Husada Indonesia, 2017)
Accident is an incident which is undesirable and unpredictable initially which can lead to loss of time, property, or the property or fatalities. The purpose of this study was to determine the relationship between compliance with PPE use with the incidence of occupational accidents on construction workers PT. PLN Persero APP Cawang type of research is explanary research with cross sectional approach. The population is all construction workers of PT. PLN Persero APP Cawang Sample of respondents used random sampling technique. The instrument used was a questionnaire. Data analysis was performed using univariate and bivariate (Fisher's test was used alternate with α = 0.05). The results of this study, the variables associated with the incidence of occupational accidents on construction workers PT PLN Persero APP Cawang is compliance with PPE use safety helmet,safety shoes,safety harnes and safety conduktife swife.Based on the research there is a relationship between the use of personal protective equipment with the inccdence of occupational accidents with an incidence of 32 workes of percentage of 49,2 %. Based on this research, the advice given to the workers, namely, employees must observe and implement the existing regulations. Suggestions for the company is to increase supervision on the use of PPE workers and provide a warning or sanction the firm for workers who do not comply with the rules for use of PPE.